Advanced solutions of transport systems for growing mobility : 14th Scientific and Technical Conference "Transport Systems. Theory & Practice 2017" selected papers (Cham, Switzerland : Springer, 2018)
What are the parameters that should be taken into account in an advanced simulation model designed for a transport system that promotes green travelling policies? How can the goal of modal shift be pursued through ICT solutions? Is it enough to apply only a single criterion when planning transport systems? What is the importance of information acquisition and provision in Intelligent Transport Systems? Answers to these and many other questions can be found in this publication. It also contains numerous analyses based on relevant data sets, illustrating the close relationship between ITS and the changes observed in terms of how specific means of transport are used. What proves to be particularly important for advanced transport systems is the use of environmentally friendly solutions that reduce their negative environmental impacts; accordingly, the book also addresses this aspect.
También disponible en formato EPUB